PROSES PENULISAN LONTAR TUTUR AJI SARASWATI KARYA IDA BAGUS OKA MANOBHAWA DALAM FOTOGRAFI STORY - Permana, I Kadek Dwiki Krishna; Raharjo, Anis; Pramana, I Made Bayu (Lp2mpp Isi Denpasar - Ps. Fotografi, 2022)
When technology is increasingly sophisticated and information is very easy to obtain, for example e-books via the internet. Writing using lontar that has been known before is replaced by books and e-books. In connection with the work practice of the MBKM activity program at the Janahita Mandala Ubud Foundation. The author documents photos of the program activities, namely Sarasastra and lontar conservation. In carrying out activities, the author realizes the lack of interest and information from the public regarding lontar so that there is a lack of interest in preserving cultural heritage. Therefore, the author made a photography story entitled